Biomechanical comparison of two implants for the stabilization of incomplete ossification of the humeral condyle lesions in dogs. Issue 1 (13th December 2013) - Coggeshall, Jason D.; Lewis, Daniel D.; Fitzpatrick, Noel; Conrad, Bryan P.; Swanson, Katy R.; Kim, Stanley E.; Palm, Lindsey S.; Tremolada, Giovanni; Pozzi, Antonio
<x xml:space="preserve">Abstract</x> Objective To compare biomechanical properties of (1) 4.5 mm cortical screws and Fitz Fenestrated Tubular Transcondylar (F2T2) screws; (2) normal humeri and humeri with an intracondylar osteotomy; and (3) humeri with an intracondylar osteotomy stabilized with either a 4.5 mm cortical screw or a F2T2 screw. Study Design Cadaveric biomechanical assessment. Sample Population 4.5 mm cortical screws (n = 10), 5.85 mm F2T2 screws (n = 10), and paired dog humeri (n = 40). Methods Cortical and F2T2 screws were loaded to failure in 3‐point bending. Ten pairs of humeri with or without an intracondylar osteotomy were axially loaded to failure. Ten additional pairs of humeri with an intracondylar osteotomy were alternately stabilized with a positional cortical or F2T2 screw and axially loaded to failure. Results Mean stiffness, yield load, and failure load was significantly greater (P < .001) for the F2T2 screws compared with cortical screws as well as for intact humeri compared with humeri with an intracondylar osteotomy (P < .001). There were no significant differences in mean stiffness (P = .59), yield load (P = .31), or failure load (P = .24) between humeri with stabilized intracondylar osteotomy. Conclusion Isolated F2T2 screws have superior mechanical properties to 4.5 mm cortical screws when loaded in 3‐point bending. Intracondylar osteotomy adversely affected humeral mechanical integrity. Osteotomized humeri stabilized by either screw had comparable mechanical properties.